Combining synthetic carbohydrate vaccines with cancer cell glycoengineering for effective cancer immunotherapy - Qiu, Lei (Springer-Verlag, 2012)
Tumor-associated carbohydrate antigens (TACAs) are useful targets for the development of cancer vaccines or immunotherapies. However, a major obstacle in this application of TACAs is their poor immunogenicity. To overcome the problem, a new immunotherapeutic strategy combining synthetic vaccines made of artificial TACA derivatives and metabolic glycoengineering of cancer cells to express the artificial TACA derivatives was explored. Using a murine leukemia model FBL3 with GM3 antigen as the target, it was shown that artificial GM3 N-phenylacetyl derivative (GM3NPhAc) elicited robust antigen-specific T cell-dependent immunity and that N-phenylacetyl-d-mannosamine (ManNPhAc) as the biosynthetic precursor of GM3NPhAc selectively glycoengineered cancer cells to express GM3NPhAc both in vitro and in vivo. It was also demonstrated that GM3NPhAc-specific antisera and antibodies mediated strong cytotoxicity to ManNPhAc-treated FBL3 cell. Furthermore, vaccination with a conjugate vaccine made of GM3NPhAc followed by ManNPhAc treatment could significantly suppress tumor growth and prolong the survival of tumor-bearing mouse. These results have proved the feasibility of the new cancer immunotherapeutic strategy, as well as its efficacy to cure cancer, which is of general significance.